Complete genome sequences of avian paramyxovirus serotype 6 prototype strain Hong Kong and a recent novel strain from Italy: evidence for the existence of subgroups within the serotype - Xiao, Sa (2010)
Complete genome sequences were determined for two strains of avian paramyxovirus serotype 6 (APMV-6): the prototype Hong Kong (HK) strain and a more recent isolate from Italy (IT4524-2). The genome length of strain HK is 16236 nucleotide (nt), which is the same as for the other two APMV-6 strains (FE and TW) that have been reported to date, whereas that of strain IT4524-2 is 16230 nt. The length difference in strain IT4524-2 is due to a 6-nt deletion in the downstream untranslated region of the F gene. All of these viruses follow the “rule of six”. Each genome consists of seven genes in the order of 3’N-P-M-F-SH-HN-L5’, which differs from other APMV serotypes in containing an additional gene encoding the small hydrophobic (SH) protein. Sequence comparisons revealed that strain IT4524-2 shares an unexpectedly low level of genome nt sequence identity (70%) and aggregate predicted amino acid (aa) sequence identity (79%) with other three strains, which in contrast are more closely related to each other with nt sequence 94–98% nt identity and 90–100% aggregate aa identity. Sequence analysis of the F-SH-HN genome region of two other recent Italian isolates showed that they fall in the HK/FE/TW group. The predicted signal peptide of IT4524-2 F protein lacks the N-terminal first 10 aa that are present in the other five strains. Also, the F protein cleavage site of strain IT4524-2, REPR↓L, has two dibasic aa (arginine, R) compared to the monobasic F protein cleavage site of PEPR↓L in the other strains. Reciprocal cross-hemagglutination inhibition (HI) assays using post infection chicken sera indicated that strain IT4524-2 is antigenically related to the other APMV-6 strains, but with 4- to 8-fold lower HI tiers for the test sera between strain IT4524-2 and the other APMV-6 strains. Taken together, our results indicated that the APMV-6 strains represents a single serotype with two subgroups that differ substantially based on nt and aa sequences and can be distinguished by HI assay.